Facile synthesis of CeO2/g-C3N4 nanocomposites with significantly improved visible-light photocatalytic activity for hydrogen evolution. (21st June 2019) - Liu, Xuecheng; He, Linxin; Chen, Ximin; Du, Liqiong; Gu, Xingxing; Wang, Song; Fu, Ming; Dong, Fan; Huang, Hongyu
Abstract: Ceria dioxide supported on graphitic carbon nitride (CeO2 /g-C3 N4 ) composites were facilely synthesized to be application for photocatalytic hydrogen (H2 ) generation in this present work. The physical and chemical properties of CeO2 /g-C3 N4 nanocomposites were determined via a series of characterizations. The CeO2 /g-C3 N4 composites prepared by facile thermal annealing and rotation-evaporation method exhibit excellent photocatalytic H2 evolution with visible-light illumination. The best hydrogen generation rate of CeO2 /g-C3 N4 composite with 1.5 wt% Pt is 0.83 mmol h −1  g −1, which is almost same as that of composite with 3 wt% Pt prepared by simple physical mixing method. The significantly developed photocatalytic activity of CeO2 /g-C3 N4 composite is majorly ascribed to the stronger interfacial effects with the more visible-light absorbance and faster electron transfer. This work reveals that construction of the CeO2 /g-C3 N4 composite with high disperse and close knit by the facile thermal annealing and rotation-evaporation method could be an effective method to achieve excellent photocatalytic hydrogen evolution performance. Highlights: CeO2 /g-C3 N4 had been facilely synthesized for photocatalytic H2 evolution. The photocatalytic hydrogen evolution rate of Pt–CeO2 /g-C3 N4 is 0.83 mmol h −1  g −1 . CeO2 /g-C3 N4 with the close-knit interface facilitates fast electrons transfer.